Role of Helicobacter pylori Eradication Therapy on Platelet Recovery in Chronic Immune Thrombocytopenic Purpura. (17th January 2017) - Sheema, Khan; Ikramdin, Ujjan; Arshi, Naz; Farah, Naz; Imran, Sheikh
Abstract : Background . Idiopathic thrombocytopenic purpura (ITP) is a bleeding disorder in which the immune system destroys native platelets. In this condition an autoantibody is generated against a platelet antigen. ITP affects women more often than men and is more common in children than adults. Objective . To assess the effect of Helicobacter pylori eradication therapy (HPET) on platelet count in Helicobacter pylori associated chronic immune thrombocytopenic purpura (chronic ITP) in adult. Materials and Methods . It is an interventional prospective study conducted at Liaquat University of Medical and Health Sciences, Jamshoro, from 2014 to 2015. A set of 85 patients diagnosed with chronic ITP were included in the study via convenient sampling. Patients with platelets count < 100 × 10 9 /L for >3 months were selected. They were posed to first-line investigations which comprised complete blood count (CBC) and peripheral blood smear examination followed by second-line tests including bone marrow examination and Helicobacter pylori stool specific antigen (HpSA-EIA). Standard H. pylori eradication therapy was offered and the patients were assessed at regular intervals for 6 months. Results. Of the 85 study patients, 32 (37.6%) were male and 53 (62.3%) were female. Mean ages of H. pylori positive and negative subjects were 43.89 ± 7.06 and 44.75 ± 7.91 years, respectively. Bone marrow examination confirmed the diagnosis and excluded other related BM disorders. H. pylori stool antigen (HpSA) was detected in 34 (40%) patients and hence regarded as H. pylori positive; the rest were negative. Treatment with eradication therapy significantly improved the mean platelet counts from 48.56 ± 21.7 × 10 9 /l to 94.2 ± 26.8 × 10 9 /l. Conclusion. We concluded that the anti-H. pylori eradication therapy improves blood platelet counts in chronic immune thrombocytopenia.